Estimation of geoacoustic parameters and source range using airgun sounds in the East Siberian Sea, Arctic Ocean - Lee, Dae Hyeok; Han, Dong-Gyun; Choi, Jee Woong; Son, Wuju; Yang, Eun Jin; La, Hyoung Sul; Tang, Dajun (Frontiers in Marine Science, 2024)
Dispersion is a representative property of low-frequency sound propagation over long distances in shallow-water waveguides, making dispersion curves valuable for geoacoustic inversion. This study focuses on estimating the geoacoustic parameters using the dispersion curves extracted from airgun sounds received in the East Siberian Sea. The seismic survey was conducted in September 2019 by the icebreaking research vessel R/V Araon, operated by the Korea Polar Research Institute. A single hydrophone was moored at the East Siberian Shelf, characterized by nearly range-independent shallow water (<70 m) with a hard bottom. In the spectrogram of the received sounds, the dispersion curves of the first two modes were clearly observed. Utilizing a combination of warping transform and wavelet synchrosqueezing transform these two modes were separated. Then, the geoacoustic parameters, such as sound speed and density in the sediment layer, were estimated by comparing the two modal curves extracted at a source-receiver distance of approximately 18.6 km with the predictions obtained by the KRAKEN normal-mode propagation model. Subsequently, the distances between the airgun and the receiver system in the 18.6 to 121.5 km range were estimated through the comparison between the measured modal curves and the model replicas predicted using the estimated geoacoustic parameters.